Corruption and reversal burden of proof: an insight into Article 37 of Indonesian law no. 31 of 1999 on corruption eradication - Wahyu Wiriadinata (Penerbit UKM, 2014)
This article touches on Corruption and Reversal Burden of Proof in accordance with Article 37 of Indonesian Law No. 31 of 1999 on Corruption Crime Eradication. It deals with questions on whether or not the implementation of the reversal burden of proof in corruption cases may prevent, reduce, or even eliminate crimes of corruption in Indonesia. This article also discusses on the extent of the effectiveness of the reversal burden of proof in Indonesia as laid down in the legislation. This research is based on a theoretical framework by Roscoe Pound, which suggests that law is a tool of social engineering. This theory has been cited by Muchtar Kusumaatmadja, who modified and adapted it to Indonesia conditions, making law as a social engineering medium. One of the changes could be seen in the area of burden of proof with the conventional system being replaced by a reversal one. The juridical-normative method is used in the analysis which involves the study of legislation related to reversal burden of proof. This research concludes that corruption is still rampant in Indonesia and that Article 37 has not been that effective in eradicating corruption crimes